Characterization of Pathogenic Bacterial Bioaerosols in Polluted Freshwater Lakes in Southern India: Implications for Public Health - Thomas, Jerusha Ann; Hameed, Byju; Hegde, Maitreyi (Asian Journal of Biological and Life Sciences)
Background: Bioaerosols are airborne microbial particles that pose a threat to the environment and human health. Materials and Methods: Bacterial bioaerosol samples were collected following standard protocols with a respirable dust sampler with microfibre filters from two freshwater lakes in Madurai, India - Vandiyur Lake (urban, highly polluted) and Valandur Lake (rural, less polluted). Gram staining and culture-based techniques were used to assess the bacterial diversity, Concentration (CFU/m³), and pathogenicity of the bacteria. Results and Discussion: Vandiyur Lake had higher bacterial concentrations (2.6×10⁵ CFU/m³), irregular, large colonies (57.14% Gram-negative, including Vibrio sp.), compared to Valandur Lake (1.13 × 10⁵ CFU/m³), which features smaller, circular colonies of bacteria that were balanced between Gram-positive (54.54%) and Gram-negative (45.45%). Bacillus (20%), Staphylococcus (4%), Streptococcus (8%), and Vibrio (28%), with polymicrobial mixtures, were among the taxa identified, indicating anthropogenic influence in Valandur Lake. The predominance of Gram-negative pathogens in Vandiyur Lake highlights pollution-driven microbial shifts, posing risks of respiratory and gastrointestinal infections. Conclusion: The study identified polluted water bodies as significant bioaerosol sources, with concentrations exceeding urban ambient levels. The presence of antibiotic-resistant genera (Staphylococcus, Vibrio) further emphasizes public health concerns, particularly in densely populated areas. This pivotal study in India highlights the need for pollution mitigation and focused monitoring of bioaerosols from contaminated water. Future research should employ molecular techniques to assess pathogenicity and seasonal variations, informing policymakers to reduce exposure risks. The results support integrated water-air quality management to protect public health in areas that are becoming rapidly urbanized.
Keywords: Antibiotic Resistance; Bioaerosol; Water pollution; Toxicity